Java programming - Farrell, Joyce (Australia : Course Technology Cengage Learning, 2012)
JAVA PROGRAMMING, Sixth Edition provides the beginning programmer with a guide to developing applications using the Java programming language. Java is popular among professional programmers because it can be used to build visually interesting GUI and Web-based applications. Java also provides an excellent environment for the beginning programmer -- students can quickly build useful programs while learning the basics of structured and object-oriented programming techniques. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.
Creating your first Java classes -- Using data -- Using methods, classes, and objects -- More object concepts -- Making decisions -- Looping -- Characters, strings, and the StringBuilder -- Arrays -- Advanced array concepts -- Introduction to inheritance -- Advanced inheritance concepts -- Exception handling -- File input and output -- Introduction to Swing components -- Advanced GUI topics -- Graphics -- Applets, images, and sound -- Appendixes. Working with the Java platform -- Learning about data representation -- Formatting output -- Generating random numbers -- Javadoc.
Includes index.
Keywords: JAVA (COMPUTER PROGRAM LANGUAGE)